Macrocycle‐Based Crystalline Supramolecular Assemblies Built with Intermolecular Charge‐Transfer Interactions - Wu, Jia‐Rui; Wu, Gengxin; Li, Dongxia; Yang, Ying‐Wei (Angewandte Chemie International Edition, 2023)
Synthetic macrocycles have served as principal tools for supramolecular chemistry, have greatly extended the scope of organic charge transfer (CT) complexes, and have proved to be of great practical value in the solid state during the past few years. In this Minireview, we summarize the research progress on the macrocycle‐based crystalline supramolecular assemblies primarily driven by intermolecular CT interactions (a.k.a. macrocycle‐based crystalline CT assemblies, MCCAs for short), which are classified by their donor–acceptor (D‐A) constituent elements, including simplex macrocyclic hosts, heterogeneous macrocyclic hosts, and host–guest D‐A pairs. Particular attention will be focused on their diverse functions and applications, as well as the underlying CT mechanisms from the perspective of crystal engineering. Finally, the remaining challenges and prospects are outlined. This Minireview highlights the advancements in the field of macrocycle‐based crystalline charge‐transfer assemblies, including their preparation, structures, and diverse supramolecular functions and applications, such as vapochromic behavior and supramolecular tessellations, arising from the CT state. Future perspectives and challenges of this emerging research field are also presented.